(untitled) (Bangladesh Journal of Otorhinolaryngology, 2013)
Thyroid carcinoma accounts for 1-1.5% of all childhood malignancies. These cancers are rare at ages younger than 5 years and more rare in male children. In this case report a 4 years old male child presented with right sided upper cervical neck mass for 11 months and treated as a branchial cyst. After histopathological report and further investigation he was finally diagnosed as papillary carcinoma of thyroid with metastatic right sided neck-node. DOI: http://dx.doi.org/10.3329/bjo.v19i1.14863 Bangladesh J Otorhinolaryngol 2013; 19(1): 73-77